1986
DOI: 10.1007/bf01277075
|View full text |Cite
|
Sign up to set email alerts
|

Contribution ofp-wave (3)+1 subamplitudes to4He binding energy and scattering observables below four-body breakup threshold

Abstract: Abstract. The four-body equations of Alt, Grassberger and Sandhas, in the form that the (2) + (2) subsystem amplitudes are treated by the convolution method, are solved for separable two-body interactions between nucleon pairs in the channels 3S1-3D 1 (too alone) and 1S 0. All L = 0 and L = 1 (3) + 1 subamplitudes are represented in a separable form using the energy dependent pole expansion. The contribution of p-wave (3)+ 1 subamplitudes to the 4He binding energy, threshold scattering observables and low ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[6] and show that NN P waves not only have a strong effect in n-t elastic observables, but also that both AV14 and Bonn-B are able to describe the total n-t cross section at the peak. This may be rationalized in the following manner: as we know from 3N physics, 1 H͑ d, d͒ 1 H spin observables are strongly dependent on the NN P waves, even at low energy E d , 3 MeV; most of this dependence comes through the odd parity 3N amplitudes J 2 which, as we know from very early work on the four-nucleon system [19], make up for 50% of the total n-t cross section. This is again shown in Fig.…”
mentioning
confidence: 98%
“…[6] and show that NN P waves not only have a strong effect in n-t elastic observables, but also that both AV14 and Bonn-B are able to describe the total n-t cross section at the peak. This may be rationalized in the following manner: as we know from 3N physics, 1 H͑ d, d͒ 1 H spin observables are strongly dependent on the NN P waves, even at low energy E d , 3 MeV; most of this dependence comes through the odd parity 3N amplitudes J 2 which, as we know from very early work on the four-nucleon system [19], make up for 50% of the total n-t cross section. This is again shown in Fig.…”
mentioning
confidence: 98%
“…Tjon [213] made an interesting finding, namely that the effect of p-waves in the 3N subamplitudes is not negligible for low-energy 4N scattering. This was later confirmed in an AGS calculation [216], where it was shown that the effect is particularly strong in p-3 He elastic cross sections, but also noticeable in dd → p -3 H and dd → dd reactions. These studies of low-energy 4N scattering reactions by Fonseca with the AGS approach were continued in Ref.…”
Section: N Problem: the Early Phasementioning
confidence: 60%
“…Our results will be compared to several techniques: the variational method (VAR) [23], the Hyperspherical Harmonics expansion (HH) [24][25][26][27], several types of approximations for the subsystem kernels of the four-body problem by operators of finite rank (SKFR) [28][29][30][31][32], the integrodifferential equation approaches (IDEA) and the S-wave projected integrodifferential equation (SIDE) [33,34], the Coupled-RearrangementChannel (CRC) [35], the differential Faddeev-Yakubovsky (DFY) [1,36], the FY (PW) [3], and the coupled twodimensional integral equations (2DI) [20]. Our results for the triton and α-particle binding energies are shown in Tables II-V in comparison to the results of other techniques.…”
Section: A Results For N N Potential Modelsmentioning
confidence: 99%